Efeitos da aplicabilidade de um manual educativo para ações de detecção precoce do câncer de mama - Silva, Anna Paula Sousa da (2012)
The control of breast cancer is based on risk mapping, planning and implementation of actions aimed to detect increasingly smaller tumors, providing better health care, reducing unnecessary spending and stimulating the development of educational strategies. The objective was to assess the effects of the application of an educational handbook related to early detection tests of breast cancer for women. This is a quasi-experimental study carried out in Fortaleza-CE, Brazil, in a Basic Health Unit. The study population consisted of women registered in this unit who underwent preventive gynecological examination in April and May 2011, intended for the first stage of data collection, being based on the number of gynecologic examination per month, totaling a sample of 294 women, equally distributed in intervention group and control group. Data collection happened through an interview by a KAP (knowledge, attitude and practice) survey, developed based on knowledge of early detection tests and the correct performance of them, as well as socio-demographic characteristics of participants and information about risk factors for breast cancer in these women. The study was developed in two phases for the intervention group (pre-intervention KAP survey followed by an educational session of the manual and later reading by the same participants and a return visit to post-intervention KAP), and a phase for the control group (KAP survey). The educational material used is a manual of guidelines for mastectomized women where we used the first two chapters that correspond to explanations focused on early detection tests. For statistical analysis we used SPSS program version 16.0 and data was tabulated, processed and analyzed in tables. Statistical tests were selected according to the need for data analysis, in order to achieve the proposed objectives, with reliability and validity of the instrument. After data analysis we observed the homogeneity of both groups, showing the association of socio-demographic variables and variables related to risk factors for developing breast cancer. However, we could verify significant differences in scores, regarding the degree of knowledge, attitude and practice on the performance of examinations for early detection of breast cancer, when compared after application of the educational intervention, noticing that the post-manual intervention group presented most of the comparative variables higher than the control group and the intervention group before the handbook, which means, after the implementation of an educational handbook, there were significant changes addressed at early diagnosis of breast cancer. The study became relevant once it proposed to assess a health education strategy, in order to minimize the gaps in knowledge and performance of the examinations for early detection of breast cancer, thus improving breast health care. In this sense, we prove the thesis that the educational intervention using an educational handbook on early detection of breast cancer for women, allowed significant results in promoting breast health through secondary prevention.